A novel approach in the treatment of neonatal gastroschisis: a review of the literature and a single-center experience. (3rd May 2018) - Briganti, Vito; Luvero, Daniela; Gulia, Caterina; Piergentili, Roberto; Zaami, Simona; Buffone, Elsa Laura; Vallone, Cristina; Angioli, Roberto; Giorlandino, Claudio; Signore, Fabrizio
Abstract: Gastroschisis is a congenital abdominal wall defect and its management remains an issue. We performed a review of the literature to summarize its evaluation, management and outcome and we describe a new type of surgical reduction performed in our center without anesthesia (GA), immediately after birth, in the delivery room. Between January 2002 and March 2013, we enrolled all live born infants with gastroschisis referred to the third-level Division of Obstetrics and Gynecology "San Camillo" of Rome. Two groups of infants were identified: group 1 in which gastroschis reduction was performed by the traditional technique and group 2 in which reduction was immediately performed after birth in the delivery room without GA. Twelve infants were enrolled in group 1, and seven infants in group 2. Statistical significance was observed between the groups regarding the hospital stay, for the duration of parenteral nutrition and full oral feeds ( p = .004). Survival was similar between two groups. The reduction without GA performed immediately after birth in a delivery room encourages the relationship between the mother and her child and appears to be a safe and feasible technique in a selected group of patients with simple gastroschisis defect; for this reason, it could represent a valid alternative to traditional approach.